Civil excavations and tunnelling : a practical guide - Tatiya, Ratan (ICE Publishing, 2018)
'Civil Excavations and Tunnelling', second edition is a comprehensive guide to civil excavations at surface and subsurface levels, with or without the aid of explosives. It features descriptions of the latest methods, techniques, equipment, trends, and practices, as well as guidance on safety and the environment.